Heterogeneous catalysis : a versatile tool for the synthesis of bioactive heterocycles - Ameta, K. L.; Penoni, Andrea (Taylor & Francis, 2015)
For more than a century, bioactive heterocycles have formed one of the largest areas of research in organic chemistry. They are important from a biological and industrial point of view as well as to the understanding of life processes and efforts to improve the quality of life. Heterogeneous Catalysis: A Versatile Tool for the Synthesis of Bioactive Heterocycles highlights the recent methodologies used in the synthesis of such bioactive systems and focuses on the role of heterogeneous catalysis in the design and synthesis of various biologically active heterocyclic compounds of pharmacological.